Anti-inflammatory activity of diclofenac sodium creams formulated with powdered soap and Aloe vera - Sunday Adown; Somtochukwu Ewuzie; Henrietta Obi; Amarachi Okoli; Ifeanyi Okeke; Calistus Nwakile (Journal of Preventive and Complementary Medicine)
Background: Sodium lauryl sulfate (SLS) has traditionally been used as an ingredient in cosmetic creams; however, its potential to cause skin sensitivity and irritation in some users raises concerns about its suitability. Additionally, aqueous cosmetic creams often suffer from instability due to their formulation, suggesting that alternative vehicles may be more appropriate.Objectives: This preclinical experimental study aims to evaluate the feasibility of substituting SLS with powdered soap (PS) for the production of intermediate emulsifying waxes and replacing purified water with Aloe vera fluid in cream formulations.Methods: Emulsifying waxes were produced using SLS and varying concentrations of PS, which were then assessed primarily through skin reactivity tests. Batch 1 consisted of an aqueous placebo cream formulated with SLS-based wax (without Aloe vera or active drug). Subsequent emulsifying waxes containing PS were utilized to create additional formulations: an aqueous placebo cream (Batch 2), an Aloe vera-based cream without active drug (Batch 3), an Aloe vera-based diclofenac sodium cream (Batch 4), and an aqueous diclofenac sodium cream (Batch 5). These cream batches were evaluated for homogeneity, color, physical stability, pH, viscosity, and spreadability over several months. Ethical approval was secured for the use of animal subjects. Anti-inflammatory activity was assessed using a formaldehyde-induced subacute inflammation model in rats over a seven-day period.Results: all emulsifying waxes were consistent, with the SLS-based wax exhibiting the highest melting point at 63 ± 2ºC. Notably, the SLS-based wax elicited a skin reaction during sensitivity testing, while the PS-based wax did not. Furthermore, it was observed that increasing concentrations of PS in the emulsifying wax correlated with lower pH levels in the resulting creams. Throughout the assessment period, all cream batches maintained a white, homogeneous, and smooth appearance. All formulations demonstrated anti-inflammatory activity; specifically, the Aloe vera-based cream (Batch 3) exhibited an inflammation index of 0.62, which was significantly lower than the placebo values of 0.70 and 0.68 for Batches 1 and 2, respectively (P<0.05).Conclusion: Powdered soap may serve as a more suitable alternative to SLS for producing emulsifying waxes and creams. Aloe vera-based creams showed enhanced anti-inflammatory activity compared to aqueous-based formulations and may provide a superior vehicle for diclofenac sodium creams. The inclusion of Aloe vera may enhance the pharmacological properties of anti-inflammatory topical preparations.